Names as Persons: A Reflection on the Normative Character of Naming in the Debate of Personhood in African Philosophy - Asia, Emmanuel; Orumwensen, Eguasa Ogiamien (NIU Journal of Humanities, 2026)
This paper examines the question of personhood in African philosophy. It evaluates the debate between Menkiti-Gyekye which latter gave birth to two distinguish but related schools of thought in African philosophy of personhood. The work argues that the cleavage between the two schools of thought is an artificial one contrary to the watertight distinction found in the ideas of some scholars say (Molefe 2019, Ikuenobe, 2006; Gyekye, 1992; Matolino; 2014). Furthermore, this work avers that the neglect of the normative and metaphysical character of naming in the debate of African philosophy of personhood attest to the inability of thinkers to resolve the problem. Hence, a careful analysis of the notion of names and naming in African philosophy will dissolve the problem of personhood in African philosophy. Keywords: African philosophy, Personhood, Names, normative, metaphysical, communitarianism, individualism.